Pemegang Saham Yang Meninggal Dunia Pada Perseroan Terbatas - Rokfa, Afida Ainur; Sumedi, Mohammad; Anugerah, Dian Purnama (Widya Yuridika, 2024)
The research was conducted because there was a legal vacuum regarding the transfer of rights to shares in PT Individuals as a result of the shareholder's death by using normative juridical research methods with statutory, conceptual and comparative approaches. The result is that PT Perorangan shares are inherited objects. PT Perorangan shareholders must be individuals, 17 years old, and legally competent. The transfer of shares of PT Perorangan resulted in changes to the company's status and data. The status of PT Perorangan remains as PT Perorangan because the object of inheritance is still joint property whose management is represented by one person, the object of inheritance falls to the heirs who are not yet competent at law, and the heirs refuse to have children. PT Perorangan changed to PT Persekutuan Modal because the heirs are more than one person and the object of inheritance has been divided. The status of PT Perorangan was lost after obtaining the determination and the liquidation report was received by the PN due to the heirs who refused to have no offspring and the object of inheritance became an unclaimed property.